PERANCANGAN COMPANY PROFILE SEKOLAH ALAM MINANGKABAU DALAM BENTUK AUDIO VISUAL - EKO PURNOMO, Syafwandi, Zubaidah A (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
AbstractSekolah alam minangkabau is a form of alternative education, where this school harness nature as the lesson that media. Sekolah alam minangkabau is first in padang city, concept Sekolah alam minangkabau is give an alternative education. Which determines that learning done in a holistic such as one of learning includes several the subject matter. Therefore to introduce and promote the sekolah alam minangkabau, needed a new draft media promotion for the sekolah alam minangkabau resources, so that future policy objectives to introduce sekolah alam minangkabau can be achieved to the target audience. The design of the main media in the form of audio visual, which lasted a little over nine minutes in DVD format that displays information sekolah alam minangkabau. Audio visual use visualization scene contains promotion about the existence of the sekolah alam minangkabau, existing facilities and activities at the school.